2016
DOI: 10.1179/1743294415y.0000000037
|View full text |Cite
|
Sign up to set email alerts
|

Drag reducing surface fabrication with deformed sharkskin morphology

Abstract: The superiority of sharkskin is the consequence of nature selection and self-evolution. The nano/ microhierarchical structure covering over sharkskin can match its living surroundings perfectly, whereas the best drag reducing effect cannot be implemented at all circumstances. Therefore, it is necessary to adjust the size and shape of sharkskin morphology to accommodate more potential flowing conditions. In this paper, the stretching deformed fabrication process of sharkskin surface is explored and investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…(a) Superhydrophobicity can possess an air barrier layer underwater like Salvinia and Notonecta glauca . , (b) Superhydrophilicity tends to attract water to form a water layer or achieve a continuous supply water barrier layer through fluid transport ( Sarracenia trichome ) whose hierarchical microchannel organization of the trichome facilitates the ultrafast water transport . (c) Lubricant can be achieved after external stimuli or constantly secrete like earthworms and sharks. , Reproduced with permission from ref , copyright 2010 Wiley; ref , copyright 2011 Beilstein-Institut; ref , copyright 2015 American Chemical Society; ref , copyright 2009 Wiley; ref , copyright 2017 Springer Nature; ref , copyright 2018 Wiley; and ref , copyright 2016 Taylor & Francis.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Superhydrophobicity can possess an air barrier layer underwater like Salvinia and Notonecta glauca . , (b) Superhydrophilicity tends to attract water to form a water layer or achieve a continuous supply water barrier layer through fluid transport ( Sarracenia trichome ) whose hierarchical microchannel organization of the trichome facilitates the ultrafast water transport . (c) Lubricant can be achieved after external stimuli or constantly secrete like earthworms and sharks. , Reproduced with permission from ref , copyright 2010 Wiley; ref , copyright 2011 Beilstein-Institut; ref , copyright 2015 American Chemical Society; ref , copyright 2009 Wiley; ref , copyright 2017 Springer Nature; ref , copyright 2018 Wiley; and ref , copyright 2016 Taylor & Francis.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, the effectiveness of riblets in drag reduction has been demonstrated in many experiments [23][24][25]. However, the spacing (s) and height (h) of the riblet are kept constant to avoid the difficulty of fabrication [26][27][28][29][30]. The spacing and height of the denticle of practical sharkskin change with the spatial gradient to better adapt to the complex fluid flow by selfadaptation [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…As emphasized by Fu et al [36], sharkskin is not a smooth surface but a kind of microgrooved surface with micro-scales called dermal denticles. Currently, research on drag reduction with microgrooved surfaces inspired by sharkskin is a hot topic [36][37][38][39]. However, with respect to airfoils or hydrofoils, most scholars have concentrated on flow field characteristics [40][41][42][43][44], and to the authors' knowledge, few studies have reported on the noise performance of airfoils with microgrooved surfaces inspired by sharkskin, which is addressed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the microgrooves of real sharkskin are not parallel to the flow direction totally. Some researchers have also investigated microgrooves or riblets across the flow direction [36,39,43,44], which is the research object in this study. The layout of this paper is as follows: Section 1 gives a brief introduction and Section 2 briefly demonstrates the theory of numerical simulation of this paper.…”
Section: Introductionmentioning
confidence: 99%